2022
DOI: 10.3389/fmicb.2022.977669
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa inhibits quorum-sensing mechanisms of soft rot pathogen Lelliottia amnigena RCE to regulate its virulence factors and biofilm formation

Abstract: The quorum-sensing (QS) cascade is responsible for the colonization and phenotypic behavior of the pathogenic organism and the regulation of diverse signal molecules. The disruption of the quorum-sensing system is an effective strategy to overcome the possibility of antibiotic resistance development in the pathogen. The quorum quenching does not kill the microbes. Instead, it hinders the expression of pathogenic traits. In the present experiment, Pseudomonas aeruginosa RKC1 was used to extract the metabolites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…Violacein production, swarming motility and biofilm formation are amongst the important quorum-sensing mediated processes in bacteria. The disruption of quorum-sensing communication networks in bacterial colonies is an effective strategy to eliminate or reduce resistance to antibiotics and it is not intended to kill bacteria but to prevent the expression of their virulence factors and pathogenicity [ 27 ]. For this reason, violacein inhibition, anti-QS, swarming inhibition and antibiofilm assays were performed at concentrations below the minimal inhibitory concentration (sub-MIC).…”
Section: Resultsmentioning
confidence: 99%
“…Violacein production, swarming motility and biofilm formation are amongst the important quorum-sensing mediated processes in bacteria. The disruption of quorum-sensing communication networks in bacterial colonies is an effective strategy to eliminate or reduce resistance to antibiotics and it is not intended to kill bacteria but to prevent the expression of their virulence factors and pathogenicity [ 27 ]. For this reason, violacein inhibition, anti-QS, swarming inhibition and antibiofilm assays were performed at concentrations below the minimal inhibitory concentration (sub-MIC).…”
Section: Resultsmentioning
confidence: 99%
“…The plant's survival during a drought is guaranteed by PGPR through a variety of mechanisms, including osmotic adjustments, increased antioxidant activity, phytohormone production, etc., and these mechanisms also promote the plant's growth. Additionally, new developments in omics technologies have improved our understanding of PGPR, which makes it easier to investigate the genes involved in colonizing plant tissue (Baba et al, 2021; Jabborova et al, 2021, 2022; Kapadia et al, 2021; Kapadia, Kachhdia, et al, 2022; Kapadia, Patel, et al, 2022; Khan et al, 2021; Khumairah et al, 2022).…”
Section: Role Of Pgpr In Combating the Abiotic Stressmentioning
confidence: 99%
“…Generally, rhizobacteria improve plant growth by synthesizing phytohormones precursors (Dodd et al, 2010; Tsukanova et al, 2017), vitamins, enzymes, siderophores, antibiotics (Prakash et al, 2022) and inhibiting ethylene synthesis. Plant growth‐promoting rhizobacteria (PGPR) promote plant development through a broad range of mechanisms, such as biological nitrogen fixation, phosphate solubilization, rhizosphere engineering, siderophore output, 1‐Aminocyclopropane‐1‐carboxylate deaminase (ACC) output, quorum sensing (QS) signal intervention, production of phytohormone and inhibition of biofilm production (Kapadia, Kachhdia, et al, 2022; Kapadia, Patel, et al, 2022), having antifungal activity, synthesis of volatile organic compounds (VOCs), promoting beneficial plant‐microbe symbioses, systemic resistance induction (Prakash et al, 2022), etc. In the present review, we highlight recent studies addressing the role of PGPR as a biofertilizer, biopesticides and photostimulation used in equitable agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclo L-prolyl-L-valine was predominantly found in the ethyl acetate extract of the Pseudomonas aeruginosa RKC1 (93.7%). This diketopiperazine (DKPs) exhibited quorum-sensing inhibition against the pathogen in liquid media during the active growth phase and regulated diverse metabolites of the pathogen (Kapadia et al, 2022). Initially, antibiotics produced by Aspergilli were referred to as aspergillin (Blumenthal., 2004), but recent studies have shown that Aspergillus oryzae can produce various secondary metabolites, such as Aspergillormarasmine, Cyclopiazonic acid (CPA), kojic acid, 3nitropropionic acid, Maltoryzine, and Violacetine, which was reported as an antibiotic produced on malt extracts (Bhumenthal, 2004).…”
Section: Discussionmentioning
confidence: 99%